Integrating Façade Design with Perceptions of Light to Shape the Spatial Experience in Libraries: A Systematic Literature Review - Ayu Nashrhifa Salsabila; Prasetyo Wahyudie; Susy Budi Astuti (Journal of Social Research, 2026)
Natural lighting in research spaces such as libraries often only prioritizes arrangements that meet functional needs. Meanwhile, users as the subjects most affected by light quality, need visual stimuli that can influence emotional and comfort in carrying out visual-intensive activities. The facade as an exterior mediator in the interior plays a crucial role in distributing light to form the visual aesthetics and ambience of space, through the diffusion patterns and character of the light formed. This study adapted the Systematic Literature Review method to identify the relationship between facades, natural light, and visual perception in shaping spatial experience in the library. The synthesis of these findings indicates that the dimensions, position, and the complexity of façade geometry and openings affect the perception of light and visual comfort in space. The results of the synthesis of findings in the literature show that the dimensions and position of openings, as well as the complexity of patterns in facade design, affect the perception of light and visual comfort in space. The facade design and light character can modify the visual quality and meaning of the space holistically, especially in the spatial design arrangement of the library. Thus, these findings confirm that interior and facade design not only need to meet technical standards but also must integrate a user-based design approach that is oriented towards the quality of space and subjective experience.